Mathematics Teacher Training for Quality Teachers: An Appraise of Teaching Needs of Preservice Teachers - Giri, Mandhoj (Butwal Campus Journal, 2025)
The article presents the findings of a study on the teaching requirements for preservice mathematics teachers that was carried out with final semester preservice university teachers who were aspiring secondary school mathematics teachers and involved in teaching practice exercises as well as teaching mathematics at different secondary schools, preservice teachers' assessments of own teaching requirements were assessed in regard to their experiences and obstacles during teaching practice, the content and pedagogical knowledge, how the program should be run? And achievement of the program objective. The qualitative research with phenomenological approach limited only on four students studying master degree fourth semester with mathematics as a major subject in Butwal Multiple Campus Butwal. The site and the participants of the study was selected purposively for the convenience of the researcher. The research was also limited on only the interview as a tool of information collection. The result suggest that the practice teaching increased the confidence to teach mathematics and their teaching practice experiences were fun and valuable opportunities them to learn. The results also demonstrated a gap between the math teaching that preservice teachers were trained to deliver in schools and the content of the training curriculum. Discussion included a summary, suggestions for how the course could be ordered and prospective areas of the curriculum that could improve the preservice teachers' competencies.